Pengendalian Penyakit Antraknosa (Colletotrichum gloeosporioides Penz)pada Buah Jeruk Siam (Citrus nobilis var. microcarpa) dengan Menggunakan Minyak Atsiri Cengkeh dan Sereh Dapur - SURYANINGSIH, KADEK INTAN; SUDANA, I MADE; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT   Anthracnose ( Colletotrichum gloeosporioides Penz) DiseaseControlon “Siam”Orange ( Citrus nobilis var. microcarpa) by UsingEssential Oilsof CloveandLemongrass The experimental designwas used Factorial Completely Randomized Design, with two  factors: FactorI : CloveEssential Oil with six treatmentstestedconcentration of 0.2%, 0.4%, 0.6%, 0.8%, 1% andwithoutconcentration. FactorII :LemongrassEssential Oil with six treatmentstestedconcentration of 0.2%, 0.4%, 0.6%, 0.8%, 1% andwithoutconcentration. The resultsshowedthat theessential oilof cloveandlemongrassconcentrations below1% cansuppressthe growth offungi C.gloeosporioides . The minimumconcentration ofcloveessential oiltreatmentsthat block100%is0,6% andlemongrassessential oilis0,4%. The effectiveness oflemongrassessential oilis higher thancloveessential oils.   Keywords : Orange,anthracnose, clove, lemongrass
Keywords: Orange; anthracnose; clove; lemongrass